Immunological Classification of Pancreatic Carcinomas to Identify Immune Index and Provide a Strategy for Patient Stratification - Chen, Yi; Chen, Didi; Wang, Qiang; Xu, Yajing; Huang, Xiaowei; Haglund, Felix; Su, Huafang (Frontiers in Immunology, 2022)
Background: Cancer immunotherapy has produced significant clinical effects in a variety of tumors. However, Pancreatic ductal adenocarcinoma (PDAC) is widely considered to be a "cold" cancer with poor immunogenicity. Our aim is to find the detailed immune features of PDAC to seek new treatment strategies. Methods: The immune abundance of PDAC patients were evaluated by single sample gene sets enrichment analysis (ssGSEA) analysis using 119 immune gene signatures. Patients was classified into different immune subtypes (IS) according to immune gene signatures. The different response patterns to immunotherapy were analyzed in datasets. The immune index was established to reflect different degrees of immune infiltration by linear discriminant analysis (LDA) analysis. Finally, potential prognostic markers associated with immune characteristic index were identified based on weighted correlation network analysis (WGCNA) analysis. Results: Three ISs were identified in PDAC, in which IS3 had the best prognosis across three cohorts. Different expression of immune profiles among three ISs indicated the distinct responsiveness to immunotherapies in PDAC subtypes. By calculating the immune index, we found that the IS3 represented the higher immune infiltration, and vice versa (IS1). Within the investigated signatures, we identified TPX2, FANCG, CSTF2 were risk factor that could be a potential diagnostic and therapeutic targets marker in PDAC patients. Conclusions: Our findings identified immunologic subtypes of PDAC with distinct prognostic implications and established immune index to represent immune infiltrations in each subtype, which provide a strong rationale to continue the exploration immunotherapy ability and make personalized treatment decision-making in PDAC patients.